EFFECT OF HEAT STRESS ON HAEMATOLOGICAL AND IMMUNOLOGICAL PARAMETERS IN BROILER CHICKEN - Kumar, Ravi; Kinehar, Amol S; Ingle, VC; Sonkusale, Prashant; Kumar, Vipin (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Environmental stress negatively affects health condition and immunity of broiler birds. The study was envisaged to understand the effect of heat stress on haematological and immunological parameters in broiler chicken under commercial production system. During summer season significant (P<0.05) increase in total erythrocyte count (TEC) and packed cell volume (PCV) was noticed. The environmental stress did not affect haemoglobin level among different age groups, however haematocrit values had shown significantly enhanced red blood cells. The total leucocyte count (TLC) was significantly (P<0.05) reduced from third week of age. Further, humoral response against Ranikhet Disease Virus (RDV) was significantly (P<0.05) decreased in fifth week of age. The study revealed that humoral immunity was affected and significant reduction in circulating white blood cells.